The investigation of incidence and multidetector computed tomography findings of median arcuate ligament syndrome - Koc, Mustafa; Artas, Hakan; Serhatlioglu, Selami (Tubitak Scientific & Technological Research Council Turkey, 2018)
Background/aim: This study aims to evaluate the incidence and multidetector computed tomography (MDCT) findings of median arcuate ligament syndrome (MALS). Materials and methods: Between January 2010 and September 2016 a total of 4028 patients who underwent angiography for MDCT based on the clinical indications for abdominal pain were retrospectively analyzed. Results: The typical signs of MAAS were identified in a total of 141 (3.5%) patients. Among all patients, 84 (59%) were male and 57 (41%) were female. The mean age was 42 years (range: 24 to 71 years). The incidence of celiac artery stenosis was 30% to 50% in 45 patients (32%) and 51% to 90% in 96 patients (68%). Poststenotic dilatation was reported in 74 patients (52%). Collateral vascular structures from the superior mesenteric artery were observed in 5 patients (3.5%). Twenty-one patients (14.9%) underwent laparoscopic surgery with significant stenosis. Conclusion: MALS is a rare vascular pathology It is especially important to recognize the presence of MALS with an epigastric pain that increases with expiration in adults and also its etiology before interventional procedures. MDCT visualization made the diagnosis of MALS easy.
Keywords: Median arcuate ligament; celiac artery; multidetector computed tomography